Ethnocultural factors in substance abuse treatment - Ashenberg Straussner, Shulamith Lala (Guilford Press New YorkUS, 2001)
Provides an introduction to ethnocultural issues as they apply to alcohol and other drug (AOD) related problems and treatment approaches. Explores concepts such as race, culture and ethnicity. Focuses on variables such as social class, encounters with prejudice, migration, acculturation, language, socieconomic status, family roles and gender and examines their relationship to substance abuse problems and their implications for treatment.